Fast 3-D Imaging of Brain Organoids With a New Single-Objective Planar-Illumination Two-Photon Microscope - Rakotoson, Irina; Delhomme, Brigitte; Djian, Philippe; Deeg, Andreas; Brunstein, Maia; Seebacher, Christian; Uhl, Rainer; Ricard, Clément; Oheim, Martin (Frontiers in Neuroanatomy, 2019)
Human inducible pluripotent stem cells (hiPSCs) hold a large potential for disease modeling. hiPSC-derived human astrocyte and neuronal cultures permit investigations of neural signal-ing pathways with subcellular resolution. Combinatorial cultures, and three-dimensional (3-D) embryonic bodies enlarge the scope of investigations to multi-cellular phenomena. A the highest level of complexity, brain organoids that – in many aspects – recapitulate anatomical and functional features of the developing brain permit the study of developmental and morphological aspects of human disease. An ideal microscope for 3-D tissue imaging at these different scales would combine features from both confocal laser-scanning and light-sheet microscopes: a micrometric optical sectioning capacity and sub-micrometric spatial re-solution, a large field of view and high frame rate, and a low degree of invasiveness, i.e., ideally, a better photon efficiency than that of a confocal microscope. In the present work, we describe such an instrument that uses planar two-photon (2P) excitation. Its particularity is that – unlike two- or three-lens light-sheet microscopes – it uses a single, low-magnification, high-numerical aperture objective for the generation and scanning of a virtual light sheet. The microscope builds on a modified Nipkow-Petráň spinning-disk scheme for achieving wide-field excitation. However, unlike the Yokogawa design that uses a tandem disk, our concept combines micro lenses, dichroic mirrors and detection pinholes on a single disk. This new design, advantageous for 2P excitation, circumvents problems arising with the tandem disk from the large wavelength-difference between the infrared excitation light and visible fluorescence. 2P fluorescence excited by the light sheet is collected with the same objective and imaged onto a fast sCMOS camera. We demonstrate 3-D imaging of TO-PRO3-stained embryonic bodies and of brain organoids, uncleared and after rapid partial transparisation with triethanolamine formamide (RTF) and we compare the performance of our instrument to that of a confocal laser-scanning microscope having a similar numerical aperture. Our large-field 2P-spinning disk microscope permits one order of magnitude faster imaging, affords less photobleaching and permits better depth penetration than a confocal microscope with similar spatial resolution.